Molecular weights of adrenocorticotropic hormone in extracts of anterior and intermediate-posterior lobes of mouse pituitary. - Mains, R E (1975)
The molecular weight of the adrenocorticotropic hormone (ACTH) activity in extracts of the separated anterior and intermediate-posterior lobes of the mouse pituitary was determined by gel filtration in guanidine-HCl. Following dilution or removal of the guanidine-HCl, ACTH activity was quantitated by both radioimmunoassay and bioassay. Extracts of the intermediate-posterior lobe contain approximately a tenth as much ACTH activity as extracts of the anterior lobe. In extracts of both the anterior and the intermediate-posterior lobes, about half of the immunological ACTH activity is similar in size to porcine ACTH (molecular weight 4000--5500). Two higher molecular weight forms of ACTH account for the remainder of the ACTH activity. About 40% of the immunological ACTH activity in anterior lobe extracts has a molecular weight of 6500--9000. Extracts of both the anterior lobe and the intermediate-posterior lobe contain ACTH activity with a molecular weight of 20,000--30,000. While this 20,000--30,000 molecular weight ACTH accounts for only 5% of the immunological ACTH activity in the anterior lobe extracts, it accounts for half of the immunological ACTH activity in extracts of the intermediate-posterior lobe. Extracts of an ACTH-secreting mouse pituitary tumor cell line (AtT-20/D-16v) contain the same three molecular weight forms of ACTH. Each of the three molecular weight forms of ACTH has a characteristic ratio of biological ACTH activity to immunological ACTH activity, independent of the source of the material (anterior lobe, intermediate-posterior lobe, or mouse pituitary tumor cell line).